From: RIKA fazi on 14 Feb 2010 14:03 % sum[(-1)^i* factorial(M-1,i)* sum ( prod(k-m) )] % i=0->M-1 j=0toM-1,j<>i k=0toM-1,k<>j % sum [of sum of (prod)] % for fixed M; m varies from 0 to M-1; % example M=5 % i=0; k=0,1,2,3,4; m=1 % (-1)^i*bin(4,i)*sum( j=0 (0-m)(1-m)(2-m)(3-m)(4-m)/(0-m) is nul because i=j % ( j=1 (0-m)(1-m)(2-m)(3-m)(4-m)/(1-m) is not nul i and j differe % ( j=2 (0-m)(1-m)(2-m)(3-m)(4-m)/(2-m) is not nul i and j differe % ( j=3 (0-m)(1-m)(2-m)(3-m)(4-m)/(3-m) is not nul i and j differe % ( j=4 (0-m)(1-m)(2-m)(3-m)(4-m)/(4-m) is not nul i and j differe % prod(k-m) for k varying from 0 to M-1 with k not equal to m %we can use the function nonzeros for force k not equal to m c21=1; for k=0:M-1 c21=c21*prod(nonzeros(k-m)); end c1c=c21; C1=0; %%% intialize the external sum for i=0:M-1 c212=0;c210=0; for j=0:M-1 djm=eq(j,m); dij=eq(i,j); if dij>=1 %% if i=j then the product is nul cc1=0; %% that is cc1=0 elseif (dij<=0) % if i and j are different if djm>=1 % then if j and m are equal we take the same product c210=c1c; elseif djm<=0 % else that is j and m different we divide the product by j-m c211=c1c./(j-m) ; c212=c212+sum(c211); % sum all product cc1=(-1).^i*bin(M-1,i)*(c210+c212); % multiply the sum by (-1)^i*bin(M-1,i) C11=cc1; end end end C1=C1+C11; end C1=C1
|
Pages: 1 Prev: meshc(x,y,z,v) plot is ignoring the "v" vector Next: please what is the name of this method |